Melanoma metastasis to the bladder: A case report - Raj A. Kumar (Elsevier, 2022)
Metastasis of malignant melanoma to the bladder is rarely seen clinically with only 29 cases reported in English-language literature. However, autopsy series of melanoma patients have shown that metastasis to the bladder could be as high as 37%, implying that numerous cases remain undiagnosed. This report details a case of malignant melanoma metastasis to the bladder. Patient presented with severe anemia and history of gross hematuria. Computerized tomography (CT) revealed a 2.7 cm mass in the bladder. Cystoscopy confirmed presence of a mass. Patient underwent cystoscopy and transurethral resection of the tumor, revealed to be melanoma on pathology.